Prevention of maternal-infant hepatitis B virus transmission by immunization: The role of serum hepatitis B virus DNA - Shou‐Dong Lee; Kwang‐Juei Lo; Jaw‐Ching Wu; Yang‐Te Tsai; Jiin-Yu Wang; Ling‐Pai Ting; Myron J. Tong (1986)
Sera from 108 HBsAg carrier mothers at delivery and their respective offspring at birth and at 6 months of age were examined for hepatitis B virus DNA by the dot-blot hybridization technique. Hepatitis B virus DNA was detected in 83% of 88 carrier mothers who were HBeAg positive, and in 10% of 20 carrier mothers who were HBeAg negative. All five infants born to HBeAg-positive carrier mothers with hepatitis B virus DNA levels over 80 pg per 10 μl of serum were infected by hepatitis B virus, in spite of receiving hepatitis B immunization. All 17 infants without hepatitis B immunization who were born to HBeAg and hepatitis B virus DNA-positive carrier mothers developed hepatitis B virus infection. Of 56 infants born to HBeAg and hepatitis B virus DNA-positive carrier mothers and who had received hepatitis B immunization, a higher hepatitis B virus infection rate was found in a group of infants whose sera hepatitis B virus DNA were positive (15/16, 93.8%) than in infants whose sera were negative (17/40, 42.5%) at birth (p<0.0005). These data suggest that the assay for hepatitis B virus DNA in sera of HBsAg carrier mothers at delivery or their infants at birth will predict the efficacy of hepatitis B immunization for prevention of maternal-infant hepatitis B virus transmission.